Letter to the reader. Self-referential strategies in Carmen Martín Gaite’s "Lo que queda enterrado" - Licci, Chiara (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article aims to offer a discursive analysis of the story "Lo que queda enterrado" (1958) by Carmen Martín Gaite, through which we will study some self-referential strategies. The author creates an implicit meaning in this text, of a metaliterary nature, a feature in which the critics have not gone in depth so far.